Antimicrobial and anti-inflammatory effects of Eugenia brejoensis essential oil in mice wounds infected by Staphylococcus aureus - Diniz, Roseana Muniz; Fernandes, Tatiany Gomes Ferreira; Mendonça, Juliana Silva Pereira; Silva, Lucas dos Santos; Saminez, Warlison Felipe de Silva; Oliveira, Patrícia Vieira de; Amorim, Erika Alves Da Fonseca; Figueiredo, Cristiane Santos Silva e Silva; Bezerra Filho, Clovis Macêdo; Correia, Maria Tereza dos Santos; Silva, Márcia Vanusa da; Sá Sousa, Joicy Cortez de; et al. (Frontiers in Pharmacology, 2022)
Eugenia brejoensis L. (Myrtaceae) is source of an essential oil (EbEO) with anti-infective activities against Staphylococcus aureus. This study evaluated the antimicrobial and anti-inflammatory potentials of EbEO in S. aureus-infected skin wounds. Swiss mice (6 to 8-week-old) that were allocated into 3 groups (n = 12): (i) non-infected wounds (CON); (ii) wounds infected with S. aureus (Sa); (iii) S. aureus-infected wounds and treated with EbEO (Sa + EbEO). The excisional lesions (64 mm2) were induced on mice back, followed by S. aureus infection (104 CFU/wound). The animals were treated with EbEO (10 µg/wound/day) or vehicle from the 1-day post-infection (dpi) until the 10th dpi. The clinical parameters (wound area, presence of exudate, edema intensity, etc.) were daily analyzed. The levels of inflammatory mediators (cytokines, nitric oxide, VEGF) and bacterial load were measured at the cutaneous tissue at 4th dpi and 10th dpi. Topical application of EbEO accelerated wound contraction with an average contraction of 83.48 ± 11.27 % of the lesion area until 6th dpi. In this period, the rates of lesion contraction were 54.28 ± 5.57% and 34.5 ± 2.67% for CON and Sa groups, respectively. The positive effects of EbEO on wound contraction were associated with significantly reduction on bacterial load and the release of inflammatory mediators (IL-6, IL-17A, TNF-α, NO and VEGF). Taken together, these data confirm the antimicrobial potential of EbEO and provide insights into its anti-inflammatory effects, making this essential oil an interesting candidate for the development of new therapeutic alternatives for infected cutaneous wounds.